On the Collocation Methods for High-Order Volterra Integro-Differential Equations (Journal of Computational Mathematics, 1990)
We study the numerical solution of high-order Volterra integro-differential equations by means of collocation techniques in certain polynomial spline spaces. The attainable order of global convergence and local superconvergence of these methods is analyzed.